Economic Turbulence in Indonesia: The Effects of Instability and Crisis - Ghannili, Farawi; Utama, Muhammad Budi; Amirullah, Malik Abd Karim; Iman, Moh Nurul (Faculty of Economic and Business, Universitas Islam Negeri Syarif Hidayatullah Jakarta, 2025)
Research Originality: This study presents a novel perspective by examining Indonesia’s economic growth over three crisis periods. It uniquely highlights how global economic uncertainty can strengthen Indonesia’s growth resilience when met with credible domestic policy responses. Research Objectives: The research investigates the effects of exports, imports, production value, interest rates, economic globalization, exchange rates, and state obligations on Indonesia’s economic growth at constant prices. Research Methods: Using quarterly time-series data from 1991Q1 to 2024Q1, the study employs a Dummy Variable–Autoregressive Distributed Lag model. Empirical Result: Exports have a direct negative effect on economic growth but when influenced indirectly by the global crisis and the pandemic, exports can actually contribute to growth. On the other hand, imports directly boost growth, but their impact is negatively affected by the global crisis. Additionally, interest rates support long-term growth but hinder it in the short run; however, crises may moderate this impact positively. Implications: These findings underscore the need for policymakers to craft dynamic, adaptable economic strategies that can safeguard Indonesia’s growth against future global shocks and uncertainties. JEL Classification: F41, E32, O53